Deep Eutectic Solvents and Nonconventional Technologies for Blueberry-Peel Extraction: Kinetics, Anthocyanin Stability, and Antiproliferative Activity - Giorgio Grillo; Veronika Gunjević; Kristina Radošević; Ivana Radojčić Redovniković; Giancarlo Cravotto (Antioxidants, 2020)
Interest in bioactive phytochemicals and sustainable processes is the driving force behind this study on two novel green extraction methods for the recovery of anthocyanins from the residues of blueberry processing. Five natural deep eutectic solvents (NADES) have been tested for anthocyanin extraction. Acidified hydroalcoholic solutions were used as benchmarks and the shelf life of eutectic systems was monitored. The most promising NADES was tested in microwave (MAE)- and ultrasound-assisted extractions (UAEs), and Peleg’s kinetic model was used. Both the enabling technologies provided performance that was superior to that of conventional extraction. MAE and UAE yielded up to 25.83 and 21.18 mg/gmatrix of total anthocyanin content, respectively, after 15 and 30 min. Moreover, a preliminary test for extract concentration and NADES recycling was performed using resin adsorption. Finally, the antiproliferative activity of the extracts was determined by a CellTiter 96® AQueous One Solution Cell Proliferation Assay, the so-called MTS assay, on human tumour HeLa cells and human skin HaCaT cells. Nonconventional extracts exhibited strong antiproliferative activity that was much greater than that of their conventionally extracted analogues. Flow cytometry was used to evaluate cell-death type, and apoptosis was found to be the primary cause of tumour cell death. The presented study demonstrates that the implementation of enabling extraction technologies and green solvents can produce an antiproliferative agent from a food industry byproduct.